The length-weight correlation and population dynamics of razor clams (Solen regularis) in Surabaya east coast, Indonesia - NINIS TRISYANI; ENDANG YULI HERAWATI; MAHENO SRI WIDODO; DADUK SETYOHADI (Society for Indonesian Biodiversity, 2016)
Trisyani N, Herawati EY, Widodo MS, Setyohadi D. 2016. The length-weight correlation and population dynamics of razor clams (Solen regularis) in Surabaya east coast, Indonesia. Biodiversitas 17: 808-813. Solen regularis is a pelecypod species living in intertidal areas at sandy substrate. In Surabaya east coast, Solen regularis is exploited by the locals for consumption, both as freshseafood or processed one. This research aims to analyze the length-weight correlation of the clams and the population dynamics, conducted from August 2014 to July 2015 in Surabaya east coast. The results show that the correlation is explained in the equation W = 0.038L2.798with the correlation coefficient of 0.9. Also, the allometric growth pattern is proven negative as the increase in body length is faster than that in weight. Growth is measured with von Bertalanffy growth model Lt = 8.0 ( 1-e (-0.7(t+0.003)) and the result from the parameter analysis using ELEFAN I method in FISAT II software show that Lâˆž = 8.0 cm and k = 0.7/year. The estimated weight at t0 in Paulyâ€™s empirical formula is -0.003 cm. Mortality rates are shown as follows: natural mortality (M) is 2.05/year, fishing mortality (F) is 2.01/year, and total mortality is 4.05/year. Exploitation rate (E) is 0.50/year indicating that the exploitation of Solen regularis is inoptimal condition. The B/R and Y/R value is 1.4%/year. It can be suggested from the findings of the research that knowledge on population dynamics may be useful for the utilization and management of Solen regularis in order to preserve its environmental and ecological sustainability.Keywords: Growth, mortality, razor clams, Solen regularis, Surabaya east coast